Fundamental Analysis of Banking Financial Performance: A Longitudinal Study of PT Bank BNI (Persero) - Anwar Ramli (Pondok pesantren As-salafiyah As-Safi'iyyah, 2026)
Banking is a strategic sector in supporting the national economy through its financial intermediation function. Bank financial performance can be evaluated using financial ratios sourced from financial statements. This study aims to examine the liquidity, solvency, and profitability of PT Bank Negara Indonesia (Persero) Tbk during the 2021–2025 period, and analyse their implications for the stability and sustainability of the bank's financial performance. The novelty of this study lies in its single-bank longitudinal approach covering a complete five-year economic cycle from post COVID 19 pandemic recovery through credit expansion to the correction phase a scope not addressed in any prior study on BNI or comparable Indonesian state-owned banks. Unlike previous multi-bank studies that produce industry-average conclusions (Putra & Wibowo, 2021; Sari & Idrus, 2023), this study offers deeper institution-specific trend analysis and contextualizes performance dynamics with BNI's distinct management policies. The method used is descriptive quantitative with secondary data in the form of consolidated annual financial statements published by BNI and the Indonesian Stock Exchange. The ratios analysed include the Loan to Deposit Ratio (LDR), Quick Ratio, Capital Adequacy Ratio (CAR), Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM). All profitability ratios are calculated consistently using consolidated financial statement data, except for CAR, which refers to Bank Only data as published by the Financial Services Authority (OJK). The results show that the LDR experienced a significant increase until 2024 (96.32%) before improving to 86.42% in 2025. BNI's solvency is very strong with a CAR ranging from 19.3%–22.0%, far exceeding the OJK minimum requirements. Profitability shows a recovery trend from ROA of 1.14% (2021) to 1.94% (2023), before being corrected to 1.48% (2025) due to increases in the cost of funds and operating expenses. Overall, BNI's financial performance is considered stable and healthy, but requires strengthening operational efficiency and credit management to maintain long-term competitiveness.